The Influence of Computer Experience and Screen Size on Use Performance and Perceptions of a Tablet-Based Chronic Illness Self-Management System for Older Adults. Issue 1 (June 2014) - Tao, D.; Or, C. K. L.; Li, K.
A usability study of a tablet-based chronic illness self-management system was conducted to evaluate the system's usability and to examine the effects of screen size and computer experience on use performance and perceptions of the system. A two-factor, between-subjects design was implemented, in which 40 older adults aged from 55 to 88 years were equally assigned to two screen size groups and required to perform a set of self-management tasks. The results showed that screen size had no effect on either the use performance or perceptions of the system, and that computer experience had significant effects on the former but no effect on the latter. Older adults without computer experience tended to perceive the large tablet screen system as more useful. This study verified the usability of the tablet-based self-management system with older adults. Its findings suggest the need to determine an optimal screen size for consumer health information technologies, and highlight the importance of computer experience in usability studies. Future studies may address its limitations.